Hubungan Antara Daya Juang Dengan Prokrastinasi Akademik Pada Mahasiswa Tingkat Akhir Yang Mengerjakan Skripsi - Anggraini, Windri Novita; , Dr. Wiwien Dinar Pratisti, M.Si, Psi (2017)
Academic procrastination is the behavior of individuals who delay in starting work and complete the task. One of the factors that affect academic procrastination is fighting spirit. This research aims to know correlation between fighting spirit with academic procrastination, the level of fighting spirit in working on the reasearch paper, the level of academic procrastination in working on research paper and the effective contribution from fighting spirit to academic procrastination. Researcher use quantitative methods to achieve the objectives of this research. The subjects used in this research was all students of The Faculty of Psychology, Muhammadiyah University of Surakarta who are taking the research paper which total 134 students. The results of the correlation coefficient (r) of -0.774 with a significance (p) = 0.000 (p <0.01). This indicates that there is a significant negative relationship between fighting spirit with academic procrastination. Based on the results analysis of academic procrastination variables have an empirical average (RE) 69.51 and a hypothetical average (RH) of 80 which means academic procrastination behavior of research subjects categorized as low. The variable fighting spirit has the empirical average (RE) of 88.68 and the hypothetical average (RH) of 75 which means fighting spirit of research subjects is high. The effective contribution from fighting spirit reached 59.9% to academic procrastination.